الأفعال الثلاثية المزيدة ودلالاتها: ‎دراسة تحليلية في المعاجم الثنائية ‏العربية الملايوية - Nurazzelena binti Abdullah (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research aims at studying the augmented triliteral verbs and their semantic connotations in order to arrive at a precise understanding of the concept of augmentation of Arabic verbs, knowing the level of prevalence of all the augmented triliteral verbs as well as understanding their theoretical indications in Malay mentality as most Arabic grammar books mention that a triliteral verb can be transformed into its augmented forms by adding one or two or three letters to the original form and that each of these augmented patterns has special connotations of transitive, causative, reciprocal, exaggerative, reflaxive, requestive, inchoative, etc. The research has adopted descriptive statistical analytical approach where it has calculated the percentage of prevalence of the augmented triliteral verbs in selected Arabic lexicons as well as figured out the criteria of their entry selection, and then analyzed the meanings of some of the selected verbs. Statistics show that the most common patterns of Arabic augmented triliteral verbs are the patterns of (أفعل) followed by (فعل) and (تفعل). The study found that most of the augmented patterns are based on hearing and not on analogy (القياس) except a few of those approved by recognized board of Arabic language. It is also proven from the analysis the hardship of expressing the implicit connotations of some of the Arabic augmented triliteral verbs in the Malay context.